Better red : the writing and resistance of Tillie Olsen and Meridel Le Sueur - Coiner, Constance (OUP E-Books., 1995)
Better Red is an interdisciplinary study addressing the complicated intersection of American feminism and the political left as refracted in Tillie Olsen's and Meridel Le Sueur's lives and literary texts. The first book-length study to explore these feminist writers' ties to the American Communist Party, it contributes to a reenvisioning of 1930s U.S. Communism as well as to efforts to promote working-class writing as a legitimate category of literary analysis. At once loyal members of the male-dominated Communist party and emerging feminists, Olsen and Le Sueur exhibit in their writing tendencies both toward and away from Party tenets and attitudes-at points subverting formalist as well as orthodox Marxist literary categories. By producing working-class discourse, Olsen and Le Sueur challenge the bourgeois assumptions-often masked as classless and universal-of much canonical literature; and by creating working-class women's writing, they problematize the patriarchal nature of the Left and the masculinist assumptions of much proletarian literature, anticipating the concerns of "second wave" feminists a generation later.